Analisis Kepuasan Kerja Terhadap Turnover Intention Karyawan Generasi Z di Perusahaan Swasta Indonesia - Surman; Nayla Zalianty; Bilfina Safira Arum Putri; Arista Avanda Fadhilah; Novi Massayu (Indo-MathEdu Intellectuals Journal, 2026)
The high employee turnover rate among Generation Z represents a strategic challenge for human resource management in Indonesia. Accordingly, this study aims to analyze and synthesize findings from various scientific literature regarding the influence of job satisfaction dimensions on turnover intention among Generation Z employees in Indonesian private sector companies. This study uses a descriptive qualitative approach with a systematic literature review of 15 national and international scientific journal articles (2019 – 2025) which were analyzed through narrative synthesis. This study identifies five primary dimensions of job satisfaction with the most significant influence: career development opportunities, work life balance, alignment between organizational culture and personal values, competitive and equitable compensation, and the quality of interpersonal relationships. The synthesized findings consistently confirm that job satisfaction has a significant negative relationship with turnover intention, whereby higher levels of job satisfaction among Generation Z employees correspond to a lower intention to leave the organization. Furthermore, Generation Z was found to exhibit a lower tolerance threshold for job dissatisfaction compared to preceding generations. These findings underscore the importance of private sector companies in Indonesia designing retention programs that are adaptive, transparent, and grounded in holistic employee well being, in order to minimize the attrition of young talent.